2021
DOI: 10.5114/ada.2021.112276
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of disease activity in patients with chronic spontaneous urticaria

Abstract: Introduction: Previous studies have examined biomarkers of coagulation, inflammation and immunity in chronic spontaneous urticaria (CSU), but no recommended biomarkers for disease activity have been established yet. Aim: To find the relationship between certain laboratory parameters and disease activity in patients with CSU. Material and methods: Serum concentrations of D-dimer, C-reactive protein (CRP), C3, C4, and prothrombin time (PT), activated partial thromboplastin time (aPTT) values were measured in 44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…Kasperska-Zajac et al also recorded significantly higher serum CRP values than in healthy subjects [median 9.2 vs. 0.74 mg/L]; the median for serum CRP was lower in our study (1.25 mg/L) [ 21 ]. In our trial, CRP was not related to CSU severity at all, similar to results obtained by Plavsic et al, who did not find a significant correlation between CRP and CSU activity [ 27 ]. The limitations of both studies could be the small number of patients enrolled.…”
Section: Discussionsupporting
confidence: 91%
“…Kasperska-Zajac et al also recorded significantly higher serum CRP values than in healthy subjects [median 9.2 vs. 0.74 mg/L]; the median for serum CRP was lower in our study (1.25 mg/L) [ 21 ]. In our trial, CRP was not related to CSU severity at all, similar to results obtained by Plavsic et al, who did not find a significant correlation between CRP and CSU activity [ 27 ]. The limitations of both studies could be the small number of patients enrolled.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies on CRP levels in CSU found them to be linked with disease activity, 8,27,32–34 but two did not 26,29 . In our study, total IgE and CRP levels were highest in severe disease and lowest in mild disease activity.…”
Section: Discussioncontrasting
confidence: 66%
“…Most studies on CRP levels in CSU found them to be linked with disease activity, 8 , 27 , 32 , 33 , 34 but two did not. 26 , 29 In our study, total IgE and CRP levels were highest in severe disease and lowest in mild disease activity. However, they were not correlated with each other, which supports their association with different CSU endotypes, that is, autoallergic and autoimmune CSU.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Of them CSU type IIb which have the higher activity score, autoimmune diseases associated, longer persistence and lower responsiveness to 2 nd generation antihistamines (8,9) . Many biomarkers were explored for severity evaluation such as d dimer, C reactive Protein and ESR (10).…”
Section: Introductionmentioning
confidence: 99%